The Cleveland Clinic Experience with Supraclavicular and Popliteal Ambulatory Nerve Catheters. (2nd April 2014) - Gharabawy, Ramez; Abd-Elsayed, Alaa; Elsharkawy, Hesham; Farag, Ehab; Cummings, Kenneth; Eid, Gamal; Mendoza, Maria; Mounir-Soliman, Loran; Rosenquist, Richard; Ali Sakr Esa, Wael
Abstract : Continuous peripheral nerve blocks (CPNB) are commonly used for intraoperative and postoperative analgesia. Our study aimed at describing our experience with ambulatory peripheral nerve catheters. After Institutional Review Board approval, records for all patients discharged with supraclavicular or popliteal catheters between January 1, 2009 and December 31, 2011 were reviewed. A licensed practitioner provided verbal and written instructions to the patients prior to discharge. Daily follow-up phone calls were conducted. Patients either removed their catheters at home with real-time simultaneous telephone guidance by a member of the Acute Pain Service or had them removed by the surgeon during a regular office visit. The primary outcome of this analysis was the incidence of complications, categorized as pharmacologic, infectious, or other. The secondary outcome measure was the average daily pain score. Our study included a total of 1059 patients with ambulatory catheters (769 supraclavicular, 290 popliteal). The median infusion duration was 5 days for both groups. Forty-two possible complications were identified: 13 infectious, 23 pharmacologic, and 6 labeled as other. Two patients had retained catheters, 2 had catheter leakage, and 2 had shortness of breath. Our study showed that prolonged use of ambulatory catheters for a median period of 5 days did not lead to an increased incidence of complications.